A Case of Acute Colonic Pseudo-Obstruction (Ogilvie's Syndrome) in a Nonsurgical Patient with Plasma Cell Leukemia. (23rd November 2022) - Hamid, Akbar; Sabu, Jacob; Elhawary, Omar; Puri, Isha; Salifu, Moro; Oh, Man; Mallappallil, Mary
Abstract : Ogilvie's syndrome, also known as acute colonic pseudo-obstruction (ACPO), is a rare, nonobstructive dilation of the colon of unclear etiology. We present the case of a patient who presented with Ogilvie's syndrome and significant hypokalemia due to colonic loss despite repletion. This case report demonstrates the difficulty in diagnosis, treatment, and outcome.